Manajemen Distribusi Dana Wakaf Produktif di BMT Mandiri Sejahtera Kantor Pusat Gresik - Khurun Imroatus Sholihah; Khozainul Ulum (Universitas Islam Lamongan, 2023)
Productive waqf is permanent property that is used in production activities. The results are distributed according to the purpose of the waqf. Waqf has dual functions, namely the function of worship and social function. This research is entitled Management of Productive Waqf Fund Distribution at BMT Mandiri Sejahtera Gresik. This qualitative research uses a descriptive analytical approach, with a research focus (1) How is the distribution management of productive waqf funds in BMT Mandiri Sejahtera Gresik? (2) How is the realization of the distribution of productive waqf funds at BMT Mandiri Sejahtera Gresik? The results figure out some points. The first is the distribution management of productive waqf funds carried out by BMT Mandiri Sejahtera Gresik, namely the distribution of cash waqf funds. It is channeled directly to the community around the BMT Mandiri Sejahtera Gresik environment by having data on the people who are entitled to it. In addition, it is channeled to the construction of mosques or prayer rooms and educational institutions by submitting proposals. The second is the realization of the distribution of productive waqf funds at BMT Mandiri Sejahtera Gresik through several programs that have all been planned to be implemented. In fact, funds resulting from the management of cash waqf are not fully distributed and there is no SOP for the management of cash waqf at BMT Mandiri Sejahtera Gresik.